From a culture of homeownership to generation rent: housing discourses of young adults in Spain - Fuster-González, Nayla Denisse; Arundel, Rowan; Susino Arbucias, Joaquín (Taylor and Francis, 2018)
Across many advanced economies, changing housing dynamics have destabilized traditional adulthood transitions. This article examines how such transformations, especially in the aftermath of the economic crisis, affect fundamental societal expectations and aspirations surrounding tenure choices and home leaving. Through a series of discussion groups and interviews among young adults in Spain – a salient context of embedded homeownership culture – the study reveals how the crisis has undermined life-course transitions and upended discourses surrounding tenure norms. Homeownership has transformed from a dominant symbol of stability and security to one of dispossession and financial risk. Conversely, where pre-crisis discourses dismissed rental, the tenure is portrayed as providing more security in the face of necessary flexibility. Our research reveals that, although traditional ‘homeownership culture’ has not disappeared from the collective imaginary and appears nuanced by social class, it has become increasingly detached from leaving the parental home. The paper exposes the extent to which dominant housing discourses may be upended even within the context of a particularly embedded Southern European homeowner society. We contend that when housing dynamics are coupled with underlying transformations in aspirations and norms, there may be significant societal outcomes
Keywords: Acceso a la propiedad; Housing; Homeownership; Social class; Transition; Youth adulthood